Effects of Amiodarone and N-desethylamiodarone on Cardiac Voltage-Gated Sodium Channels - Ghovanloo, Mohammad-Reza; Abdelsayed, Mena; Ruben, Peter C. (Frontiers in Pharmacology, 2016)
Amiodarone (AMD) is a potent antiarrhythmic drug with high efficacy for treating atrial fibrillation and tachycardia. The pharmacologic profile of AMD is complex. AMD possesses biophysical characteristics of all of class I, II, III, and IV agents. Despite its adverse side effects, AMD remains the most commonly prescribed antiarrhythmic drug. AMD was described to prolong the QT interval and can lead to torsades de pointes. Our goal was to study the effects of AMD on peak and late sodium currents (INa,P and INa,L) and determine whether these effects change as AMD is metabolized into N-Desethylamiodarone (DES). We hypothesized that AMD and DES block both INa,P and INa,L with similar profiles due to structural similarities. Given the inherent small amounts of INa,L in NaV1.5, we screened AMD and DES against the Long QT-3-causing mutation, ∆KPQ, to better detect any drug-mediated effect on INa,L. Our results show that AMD and DES do not affect WT or ∆KPQ activation; however, both drugs altered the apparent valence of steady-state fast-inactivation. In addition, AMD and DES preferentially block ∆KPQ peak conductance compared to WT. Both compounds significantly increase INa,L and window currents. We conclude that both compounds have pro-arrhythmic effects on NaV1.5, especially ∆KPQ; however, DES seems to have a greater pro-arrhythmic effect than AMD.